The Role of Data-Driven Decision Making in Enhancing Organizational Resilience Post-Pandemic - Safrezi Fitra; Bilgah Bilgah; Eka Putri Handayani; M. Mahdi Alatas (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to analyze the role of data-driven decision making (DDDM) in enhancing organizational resilience post-pandemic. The COVID-19 pandemic accelerated the shift in decision-making processes, with many organizations transitioning to a data-driven approach to improve their ability to cope with uncertainty. This quantitative research used a survey involving 133 respondents from various organizations that have implemented DDDM. Data were collected using a questionnaire measuring the application of DDDM, organizational resilience, and the role of technology in supporting data-driven decision making. The results showed that DDDM has a significant positive impact on organizational resilience, with technologies such as big data and artificial intelligence (AI) playing a crucial role in enhancing this resilience. These findings provide practical implications that organizations need to strengthen their data-driven decision-making and develop their technology infrastructure to face future challenges. This study also contributes to the literature on the relationship between DDDM and organizational resilience in the post-pandemic context.